Pemberdayaan masyarakat dalam pembuatan Pupuk Organik Cair (POC) dari sampah organik di lokasi wisata Desa Rindu Hati Bengkulu Tengah - Gustria Ernis; Nola Windirah; Dyah Fitriani (Unri Conference Series: Community Engagement, 2021)
Waste from tourism activities in the village of Rindu Hati can reduce the quality and sustainability of the environment. The purpose of this program is to empower the target community in managing waste into something of use and even economic value. Organic waste if left to decompose naturally without being processed will cause a bad smell and disturb the aesthetic view. For this reason, LOF (Liquid Organic Fertilizer) is the right choice organic waste management solution. Besides not spoiling the aesthetic view, LOF can be used to fertilize any plants around the Rindu Hati Village Area. This program is carried out with the stages of socializing the types of waste, training in organic waste management into LOF and assisting and empowering the community in LOF production. Participants in the POC training are women farmer groups (KWT) in Rindu Hati Village and managers of Tourism Villages. After conducting socialization, training and mentoring, it was found that the level of knowledge and skills of the community increased. This is evidenced by the success of the community in making LOF with a fermented fragrance and no bad smell. The target community is given composter and other materials to maintain the sustainability of the program.